Public and private organizations - Wyszynski, Gloria (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2018)
In this paper author focuses on the inquiry into whether and to what degree public and private organizations differ.
Keywords: differences; similarities; organization; public; private